2012
DOI: 10.1089/neu.2011.2259
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Syringohydromyelia Induced by Adhesive Arachnoiditis in the Rabbit: Changes in the Blood–Spinal Cord Barrier, Neuroinflammatory Foci, and Syrinx Formation

Abstract: There are many histological examinations of syringohydromyelia in the literature. However, there has been very little experimental work on blood permeability in the spinal cord vessels and ultrastructural changes. We prepared an animal model of spinal adhesive arachnoiditis by injecting kaolin into the subarachnoid space at the eighth thoracic vertebra of rabbits. The animals were evaluated 4 months later. Of the 30 rabbits given kaolin injection into the cerebrospinal fluid, 23 showed complete circumferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
2
7
1
1
Order By: Relevance
“…3) and enlarged perivascular spaces (Fig. 2) reported in this study are consistent with earlier reports on the ultrastructure of human and rabbit syrinx cavities [14,15,32,33]. Interestingly, enlarged perivascular spaces were also reported in hydrocephalus [34][35][36] and a number of cerebrovascular and systemic pathologies including small vessel disease [37,38], moyamoya disease [39], ischemic and lacunar stroke [40], lupus erythematosus [41], and arteriosclerosis [42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3) and enlarged perivascular spaces (Fig. 2) reported in this study are consistent with earlier reports on the ultrastructure of human and rabbit syrinx cavities [14,15,32,33]. Interestingly, enlarged perivascular spaces were also reported in hydrocephalus [34][35][36] and a number of cerebrovascular and systemic pathologies including small vessel disease [37,38], moyamoya disease [39], ischemic and lacunar stroke [40], lupus erythematosus [41], and arteriosclerosis [42].…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by previous findings using an excitotoxic model of PTS, which demonstrated that the BSCB is permeable to vascular tracers surrounding a syrinx [31]. Further, this is consistent with findings of increased vesicular transport and endothelial tight junctional opening adjacent to syrinxes in a leporine model of adhesive arachnoiditis [32]. Overall, these studies support the hypothesis that perivascular spaces play an important role in facilitating fluid flow in the spinal cord tissue, and their integrity is compromised in PTS.…”
Section: Discussionsupporting
confidence: 88%
“…20 In an experiment with rabbits, 21 kaolin was injected into the spinal subarachnoid space to induce adhesive arachnoiditis. 20 In an experiment with rabbits, 21 kaolin was injected into the spinal subarachnoid space to induce adhesive arachnoiditis.…”
Section: Arachnoiditis and Other Experimental Modelsmentioning
confidence: 99%
“…By contrast, syringomyelia is a progressive condition associated with intramedullary ischemia and tissue necrosis causing cavitation. 3 A filiform, or slitlike, appearance on MRI is said to distinguish hydromyelia from syringomyelia, but in some series 20% of patients with filiform dilations of the central spinal cord canal show progression consistent with syringomyelia. 4 The presence of objective neurologic deficits and certain features on MRI (spinal cavity .6 mm in diameter and .5 segments in length; abnormal contrast enhancement; spinal cord expansion; cavity enlargement over time) or electrophysiologic testing (abnormalities on EMG, somatosensory evoked potentials [SSEPs], or motor evoked potentials [MEPs]) allows patients with syringomyelia to be distinguished more reliably from those with hydromyelia.…”
Section: Sectionmentioning
confidence: 99%
“…These result in macrocystic or microcystic changes. 3 Where an obvious structural cause cannot be identified, the term idiopathic syringomyelia is applied.…”
Section: Go To Sectionmentioning
confidence: 99%